2011
DOI: 10.4049/jimmunol.1001470
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Leptin Receptor–STAT3 Signaling Enhances Leukotriene Production and Pulmonary Host Defense against Pneumococcal Pneumonia

Abstract: The adipocyte-derived hormone, leptin, regulates energy homeostasis and the innate immune response. We previously reported that leptin plays a protective role in bacterial pneumonia, but the mechanisms by which leptin regulates host defense remain poorly understood. Leptin binding to its receptor, LepRb, activates multiple intracellular signaling pathways, including ERK1/2, STAT5, and STAT3. In this report, we compared the responses of wild type (WT) and s/s mice, which possess a mutant LepRb that prevents lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 62 publications
(95 reference statements)
1
43
2
Order By: Relevance
“…In combination studies, in contrast, the magnitude of improvement with active drug on top of background therapy appears to be attenuated, and the placebo-treated subjects, who continue to receive background therapy, generally remain stable or even further improve slightly; since they are less likely to deteriorate during a short trial, the magnitude of placebo-corrected treatment effect is attenuated. This explains the consistent finding of an average treatment effect of 20-25 m in combination trials (7,12,13) as compared with values twice that in most de novo treatment trials. Furthermore, there may be a dissociation between harder outcomes such as mortality and the magnitude of improvement in 6MWD with combination therapy (13).…”
Section: The 6-minute Walk Test In Pulmonary Arterial Hypertensionsupporting
confidence: 72%
See 1 more Smart Citation
“…In combination studies, in contrast, the magnitude of improvement with active drug on top of background therapy appears to be attenuated, and the placebo-treated subjects, who continue to receive background therapy, generally remain stable or even further improve slightly; since they are less likely to deteriorate during a short trial, the magnitude of placebo-corrected treatment effect is attenuated. This explains the consistent finding of an average treatment effect of 20-25 m in combination trials (7,12,13) as compared with values twice that in most de novo treatment trials. Furthermore, there may be a dissociation between harder outcomes such as mortality and the magnitude of improvement in 6MWD with combination therapy (13).…”
Section: The 6-minute Walk Test In Pulmonary Arterial Hypertensionsupporting
confidence: 72%
“…Mancuso and colleagues have shown that alveolar macrophage function is altered in leptin-deficient mice: macrophages from obese mice have impaired phagocytosis and abnormalities in leukotriene production (11,12). This has important implications for host defense.…”
mentioning
confidence: 99%
“…Binding of leptin to its receptor (LepRb) leads to activation of multiple signaling pathways via phosphorylation of different conserved tyrosine residues in the intracellular domain (50,51). In mouse models of Gram-negative bacterial pneumonia, leptin signaling via the STAT3 pathway (Y1138S-STAT3 mutant mice [S1138 mice]) was protective (32). Studies from our laboratory have also shown that S1138 mice had worse disease in a mouse model of amebic colitis (29).…”
Section: Resultsmentioning
confidence: 70%
“…Leptin was protective in the murine model via activation of STAT3/SOCS3 and SHP2/ mitogen-activated protein kinase (MAPK)-extracellular signalregulated kinase (ERK) signaling pathways downstream of the leptin receptor (29). Other investigators have shown an association of the Q223R mutation with the increased susceptibility of patients to bacterial peritonitis (42), and in murine models, leptin has been shown to protect from bacterial pneumonia (30,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation